Detecting Potential Fraudulent Financial Reporting Through Hexagon Fraud in Indonesia Insurance Companies - Lestari, Dian; Rusmanah, Enok; Sasongko, Hendro (APPS Publications, 2025)
The research aims to determine the influence of fraud hexagon elements on detecting fraudulent financial reporting. The fraud hexagon is a model for detecting fraud in financial reporting proposed by Vousinas in 2019. The model comprises six elements: pressure, opportunity, rationalization, capability, arrogance, and collusion. These elements are measured using financial stability and external pressure (pressure), nature of the industry and ineffective monitoring (opportunity), change in auditor (rationalization), change of director (capability), frequent number of Chief Executive Officer (CEO) pictures (arrogance), and political connection (collusion). The study used a sample of 85 observations from 17 insurance companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023 and investigated by using ordinary least squares regression. The results show that all elements of the fraud hexagon significantly influence fraudulent financial reporting, with collusion appearing to be the strongest influence. Therefore, it is recommended that the fraud hexagon elements be considered as fraud monitoring and prevention strategies.